Enabling technologies of health and safety practices in the fourth industrial revolution: Nigerian construction industry perspective - Abina, Oluwarotimi Gbenga; Ogunbayo, Babatunde Fatai; Aigbavboa, Clinton Ohis (Frontiers in Built Environment, 2023)
Globally, different approaches have been applied to improve workplace safety practices due to the complexities of construction activities that pose different dangers to workers' safety and well-being. This study uses Lagos, Nigeria, as a case study and investigates awareness of 4IR technologies in H&S practices among construction professionals in the Nigerian construction industry. A quantitative research approach was developed to retrieve a structured survey questionnaire from construction stakeholders in the study area. Retrieved data was analysed in three stages: data reliability and validity, descriptive statistics, and exploratory factor analysis (EFA). The descriptive analysis findings and the Kruskal-Wallis H test revealed no significant difference in professionals' awareness of 4IR technologies in H&S practices in the construction project delivery in Lagos, Nigeria. The findings of the EFA returned four-factor components of H&S practices enabling technologies in the Era of 4IR as data and robotic technologies, process-based automation, output communication technologies, and wearable hazard detectives' technologies. This study recommends innovative strategies from the professional bodies through academic and professional development (workshops, training, conferences, and seminars) to improve knowledge of 4IR technologies in H&S practices among professionals.